Canadian Pentecostals, the Trinity, and contemporary worship music: the things we sing - Tapper, Michael (Global Pentecostal and charismatic studies, 2017)
Influence of eastern and western Trinitarian thought -- Canadian Pentecostals and the Trinity -- Colin Gunton -- Critiquing Gunton's Trinitarian theology -- A framework for Trinitarian evaluation of Canadian Pentecostal music -- Lyrics and theology proper -- A Canadian Pentecostal approach to God -- Lyrics and anthropology -- A Canadian Pentecostal approach to human personhood -- Lyrics and cosmology -- A Canadian Pentecostal approach to the world -- Leading Pentecostals forward in Trinitarian thought